Digital Reproductive Health Literacy Intervention for Enhancing the Service Behavior: A Systematic Literature Review - Dheva-aksorn, Kirana; Prasittichok, Pitchada; Intarakamhang, Ungsinun (The Journal of Behavioral Science, 2024)
The World Health Organization has long recognized that reproductive health literacy (RHL) skills development for service providers is important to ensure safe sexual health behaviors and to guide appropriate sexual decisions and equality for adolescents and youths through digital services. The purpose of this research was to examine interventions for digital reproductive health literacy (DRHL) to enhance service behavior among service providers. In this study, the PRISMA guidelines was used to conduct a systematic literature review involving 622 studies, with five selected for final analysis. The results indicated that firstly, the DRHL intervention can encompass on-site, online, and group activities, accompanied by learning materials, to enhance skills in six areas: (1) promoting reproductive health knowledge among service providers; (2) developing the digital adaptation skills of service providers; (3) cultivating creative communication skills on reproductive health with adolescents through digital channels; (4) shaping the attitudes towards reproductive health in digital age service providers; (5) providing services to adolescents and youth through digital channels; and (6) enhancing team and network management skills. Secondly, DRHL was assessed based on four components; (1) accessing reproductive health information; (2) understanding reproductive health information; (3) applying reproductive health information; (4) appraising reproductive health information. Thirdly, most studies were evaluated to three phases: pretest, posttest, and follow-up assessment. The study finding demonstrated improvements in health behaviors and service behaviors in three key areas; (1) DRH knowledge, (2) skills, and (3) attitude toward service delivery.